Hierarchical Model for the Role of J-Domain Proteins in Distinct Cellular Functions. Issue 3 (5th February 2021) - Sugimoto, Shinya; Yamanaka, Kunitoshi; Niwa, Tatsuya; Terasawa, Yurika; Kinjo, Yuki; Mizunoe, Yoshimitsu; Ogura, Teru
Graphical abstract: Highlights: The specific role of JDPs in bacterial cellular functions is unclear. DnaJ, one of the JDPs in E. coli, is essential for survival at high temperature. Either DnaJ or CbpA is sufficient to activate DnaK in bacterial amyloid production. DnaJ and CbpA promote the DnaK-regulated production of curli at multiple steps. The role of JDPs in the DnaK system differs in different cellular functions. Abstract: In Escherichia coli, the major bacterial Hsp70 system consists of DnaK, three J-domain proteins (JDPs: DnaJ, CbpA, and DjlA), and nucleotide exchange factor GrpE. JDPs determine substrate specificity for the Hsp70 system; however, knowledge on their specific role in bacterial cellular functions is limited. In this study, we demonstrated the role of JDPs in bacterial survival during heat stress and the DnaK-regulated formation of curli—extracellular amyloid fibers involved in biofilm formation. Genetic analysis demonstrate that only DnaJ is essential for survival at high temperature. On the other hand, either DnaJ or CbpA, but not DjlA, is sufficient to activate DnaK in curli production. Additionally, several DnaK mutants with reduced activity are able to complement the loss of curli production in E. coli Δ dnaK, whereas they do not recover the growth defect of the mutant strain at high temperature. Biochemical analyses reveal that DnaJ and CbpA are involved in the expression of the master regulator CsgD through the solubilization of MlrA, a DNA-binding transcriptional activator for the csgD promoter. Furthermore, DnaJ and CbpA also keep CsgA in a translocation-competent state by preventing its aggregation in the cytoplasm. Our findings support a hierarchical model wherein the role of JDPs in the Hsp70 system differs according to individual cellular functions.